Real-time software framework for underwater mobile robots - Sathyavathi Ramaiah. (2008)
This thesis proposes an Object-Oriented Framework for the Software Architecture of Underwater Mobile Robots. Even with the increased interest in the development of underwater robotic technology, the design, fabrication and analysis of autonomous underwater vehicles are still very complex and expensive. The unpredictable and hazardous underwater environment is extremely unforgiving and remote. With limitations in communication, an AUV must continuously operate in autonomous modes. Thus, the development of an underwater robotic system is essential.